Clinical Study of NUVCC Sunscreen on Its Safety and Utility - Clinical Research Group of NUVCC (Skin research, 1996)
We conducted a multiple open study using NUVCC (NOV UV Care Cream D ®), a new sunscreen of SPF 15 containing super-fine titanium dioxide as ultraviolet (UV) reflactant and 0.01% hyaluronic acid for moisturizing, but no UV absorbers, to evaluate its safety and utility of NUVCC on patients with photosensitive diseases, atopic dermatitis (AD) and healthy subjects with histories of contact dermatitis. A total of 210 cases visiting 16 dermatology clinics of university hospitals of Japan used NUVCC for four weeks after informed consents. Its safety rates in photosensitive diseases was 96.3%, in AD was 85.9%, and in healthy subjects who had previous histories of contact dermatitis was 100%, respectively. Its utility in photosensitive diseases was 87.8%. The rate of side-effect (9.5%) among 210 cases was significantly lower than the rate of side-effect (18.2%) experienced previously using other sunscreens.These results indicate that NUVCC is a highly safe sunscreen recommended for AD and other subjects with sensitive skin, and is also effective for preventing sun damage in photosensitive diseases. Further, NUVCC may be safely used for children to reduce chronic adverse effects of solar radiation. 皮膚を太陽紫外線の害から護る新しいタイプのサンスクリーン剤NUVCC (ノブUVケアクリームD®) を用い, 全国16大学皮膚科で光線過敏症, アトピー性皮膚炎患者, 接触皮膚炎既往者等合計210例について臨床試験を実施した。試験試料は紫外線吸収剤を含まず, 紫外線散乱剤としての微粒子酸化チタンを主としたサンスクリーン剤でSPFは15であり保湿効果を高めるためにヒアルロン酸ナトリウムを配合している。4週間の使用試験では, 光線過敏症82例では96.3%, アトピー性皮膚炎患者85例では85.9%, 接触皮膚炎既往者25例では100%という高い割合で安全性を確認した。また光線過敏症患者では87.8%について有用性が認められた。副作用は210例中20例 (9.5%) に認められたが, 過去に本剤以外のサンスクリーン剤を用いた場合の皮膚トラブル発生率が18.2%という数値であることからも, 本剤の高い安全性がうかがえる。これらの結果から, 本製品は光線過敏症の予防や治療はもちろん, アトピー性皮膚炎患者や健康な小児の皮膚を有害な紫外線から守る目的で, 広く, 長期にわたる使用が可能であると考えられる。